PWE-082 The Impact Of Nod2 Variants On Gut Microbiota In Crohn's Disease And Healthy Controls. (9th June 2014) - Kennedy, NA; Walker, AW; Berry, SH; Lamb, CA; Lewis, S; Mansfield, J; Parkes, M; Parkhill, J; Probert, C; Read, D; Satsangi, J; Simpkins, R; et al.
Abstract : Introduction: Crohn's disease (CD) is now understood to be caused by the interaction between genetic and environmental factors with dysregulation of gut microbiota playing a pivotal role. NOD2, the strongest genetic risk factor for CD, encodes a pattern recognition receptor and plays an important role in epithelial defence. Studies of NOD2 -knockout mice have demonstrated shifts in gut microbiota. Human studies to date have been limited by relatively small numbers of individuals homozygous for NOD2 mutations without accurate matching of controls. Methods: Individuals with CD of known NOD2 status were identified from the UK IBD genetics consortium. Patients in clinical remission were selected if they carried 2 of the common NOD2 variants (homozygotes or compound heterozygotes). Each NOD2 mutant patient was matched to a NOD2 wild-type patient. For all CD patients a household control was approached. Healthy volunteers stratified by NOD2 genotype were recruited from the Cambridge Bioresource. Faecal samples were frozen within 24h of collection. DNA was extracted using the FASTDNA Spin Kit for Soil. The V1–3 region of the 16S rRNA gene was amplified and amplicons were sequenced with Illumina MiSeq. Sequence data was processed in Mothur. Calprotectin was measured in all samples by ELISA. Results: 97/107 individuals were included in the primary analysis (40 CD patients [58% NOD2 mutant], 32 bioresource volunteers [50% NOD2 mutant], 25 household controls). The minimum reads per sample were 3953, mean 21216. There was a significant reduction in diversity (inverse Simpson index), Ruminococcaceae including Faecalibacteria and increase in Enterobacteriaceae in samples from CD patients vs. controls (all p < 0.0001). There were no differences in diversity or relative abundance of any bacterial families when stratified by NOD2 status, either within the CD patients or bioresource controls. Conclusion: This study confirms previously identified shifts in gut microbiota in CD patients. However, no significant differences in gut microbiota were seen when analysed by NOD2 status. This may be a reflection of sample size or of studying gut bacteria in stool as opposed to the mucosally-associated compartment. We are presently recruiting additional cases and controls to increase study power for additional analysis. Disclosure of Interest: None Declared.